Highly Active Nanoperovskite Catalysts for Oxygen Evolution Reaction: Insights into Activity and Stability of Ba0.5Sr0.5Co0.8Fe0.2O2+δ and PrBaCo2O5+δ. (20th September 2018) - Kim, Bae‐Jung; Cheng, Xi; Abbott, Daniel F.; Fabbri, Emiliana; Bozza, Francesco; Graule, Thomas; Castelli, Ivano E.; Wiles, Luke; Danilovic, Nemanja; Ayers, Katherine E.; Marzari, Nicola; Schmidt, Thomas J.
Abstract: It is shown that producing PrBaCo2 O5+δ and Ba0.5 Sr0.5 Co0.8 Fe0.2 O2+δ nanoparticle by a scalable synthesis method leads to high mass activities for the oxygen evolution reaction (OER) with outstanding improvements by 10× and 50×, respectively, compared to those prepared via the state‐of‐the‐art synthesis method. Here, detailed comparisons at both laboratory and industrial scales show that Ba0.5 Sr0.5 Co0.8 Fe0.2 O2+δ appears to be the most active and stable perovskite catalyst under alkaline conditions, while PrBaCo2 O5+δ reveals thermodynamic instability described by the density‐functional theory based Pourbaix diagrams highlighting cation dissolution under OER conditions. Operando X‐ray absorption spectroscopy is used in parallel to monitor electronic and structural changes of the catalysts during OER. The exceptional BSCF functional stability can be correlated to its thermodynamic meta‐stability under OER conditions as highlighted by Pourbaix diagram analysis. BSCF is able to dynamically self‐reconstruct its surface, leading to formation of Co‐based oxy(hydroxide) layers while retaining its structural stability. Differently, PBCO demonstrates a high initial OER activity while it undergoes a degradation process considering its thermodynamic instability under OER conditions as anticipated by its Pourbaix diagram. Overall, this work demonstrates a synergetic approach of using both experimental and theoretical studies to understand the behavior of perovskite catalysts. Abstract : Flame Spray synthesized nanoparticles of PrBaCo2 O5+ δ and Ba0.5 Sr0.5 Co0.8 Fe0.2 O2+ δ yield superior oxygen evolution reaction activities in alkaline electrolyte than those prepared by the state‐of‐the‐art sol–gel method. The functional stabilities of these materials are also assessed and elucidated in parallel with density‐functional theory computed Pourbaix diagrams highlighting the importance of understanding cation dissolution process.